Efficacy of Reducing Recurrence of Intrauterine Adhesions and Improving Pregnancy Outcome after Hysteroscopic Adhesiolysis: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Li-jun Lin; Xiao-yong Qiao; Xue-ping Chen; Liang-zhi Xu; Hui Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: A systematic review with pairwise and network meta-analyses was conducted to compare the clinical efficacy of treatments in reducing intrauterine adhesion (IUA) recurrence and improving pregnancy outcome after hysteroscopic adhesiolysis. Methods: PubMed, Web of Science, Embase, Cochrane library, and Clinicaltrials.gov were searched electronically up to January 17th, 2024, supplemented with manual searches. Eligible studies were randomized clinical trials (RCTs) with allocation to intrauterine device (IUD), auto-cross-linked hyaluronic acid (ACP), medical chitosan (MC) + IUD, Foley (Foley balloon catheter 3–7 days) + IUD, heart shape balloon (HSB), dried amnion graft or bone marrow stem cells-scaffold or granulocyte colony-stimulating factor (DBG) + Foley/HSB, autologous platelet gel or platelet-rich plasma (APG/PRP) + IUD/HSB, ACP + Foley/IUD, Foley, and heart shape balloon or Foley 1 month (H/F) + IUD. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Pairwise meta-analyses were performed in random effects model when direct data were available; Network meta-analyses were conducted using “mvmeta” and “network” packages in Stata MP 17.0. The primary outcomes were the recurrence of IUA and clinical pregnancy. The secondary outcomes included menstrual blood volume and second-look IUA score. The research protocol was registered in PROSPERO (CRD42024502941). Results: Fifteen RCTs comprising 1827 patients randomized to ten treatment protocols were included in this study. Evidence quality was all low risk of bias. ACP and Foley + IUD (surface under the cumulative ranking curve area (SUCRA) 96.4% and 83.5%, respectively) seemed effective in reducing the recurrence of IUA, H/F + IUD and DBG + Foley/HSB (SUCRA 89.7% and 82.1%, respectively) maybe effective in improving the clinical pregnancy according to network meta-analysis. Evidence on secondary treatment outcomes was insufficient. Conclusions: Some of these protocols maybe effective in reducing the recurrence of IUA or increasing clinical pregnancy. But the result should be interpreted with caution owing to the small studies, open-loop network analysis partly, and insufficient evidence. More RCTs about DBG + Foley/HSB needs to be designed, the relative effectiveness of different degrees of IUA treatment should be further clarified, and more attention should be paid to clinical pregnancy, menstrual flow, and second-look IUA score.